Analisis Penerapan Overall Equipment Effectiveness Pada Mesin Power Press Combination Forming 60T - Rusdi Widya, Adi (Universitas Serang Raya, 2017)
Corrective action on the engine damage is a temporary emergency measure, so further action is required by conducting maintenance activities, prevention of damage (Preventive maintenance), and able to detect abnormal symptoms before the machine breakdown occurs. The sudden impact of machine damage resulted in disruption of planned production performance so that it is necessary to identify and analyze the factors that cause the machine damage. Establish maintenance method using Autonomous Maintenance, Preventive Maintenance and Reliability Centered Maintenance (RCM) concept to prevent machine failure from the beginning, through fault tree analysis (FTA) method, failure mode effect, and analysis (FMEA), mean time between failure (MTBF) is an analytical activity for implementing RCM systems on machines and critical components, able to identify and detect symptoms of malfunction before the machine is damaged. The results of the research get better application of maintenance system so that identification of important components can be anticipated from the symptoms of damage.Â Overall, there is an increase in performance seen from the increase of Overall Equipment Effectiveness (OEE) value, still expected to continue to increase according to JIPM 85% standard value. In conclusion FMEA, FTA, MTBF analysis method can be used to build autonomous maintenance, preventive maintenance and reliability centeredÂ maintenance so as to facilitate the production and maintenance in determining the proper maintenance of the machine.